Platelet-Rich Fibrin in Periodontal Regeneration - D. Kolgeci; B. Kolgeci; A. Emini; A. Kolgeci (International Journal of Biomedicine)
Background: Periodontal disease is multifactorial regarding potential etiological factors and modifiers of achieved therapeutic effects. The treatment of this disease has been a challenge for periodontists for years. In recent years, new methods have begun to be implemented to regenerate periodontal tissue. One of these methods is platelet-rich plasma therapy in regenerating periodontal tissue. This study aimed to assess the potential benefits of platelet-rich fibrin (PRF) in periodontal regeneration. Material and Methods: An electronic literature search was conducted using the National Library of Medicine, PubMed/MEDLINE, and the Scopus database, covering articles published from 2000 to 2023. Keywords used included "platelet-rich fibrin (PRF)," "PRF in periodontology," "PRF on gingival recession," and "PRF in infrabony pocket." The articles were selected based on title and abstract, focusing on clinical applications of PRF in periodontology. Inclusion criteria encompassed case reports, case series, original research, review papers, and both in vitro and in vivo studies, including animal studies and controlled clinical trials. Conclusion: The use of PRF in the treatment of periodontal diseases, especially advanced platelet-rich fibrin, offers additional benefits in periodontal regeneration. Simplicity in the preparation, minor interventions, cost efficiency, and favorable clinical results have made this treatment method attractive for the regeneration of gingival recessions and the treatment of bone defects. The relatively small volume of PRF obtained from a single blood sample and the dependence on accurate handling and preparation are limitations that must be considered.